REUSE OF THE AQUEOUS PHASE OF BIO-OIL FRACTIONATION AS A WATER-REPELLENT AGENT FOR WOOD - Sanson, Caio Silvestre Lima; Dias, Ivana Amorim; Santos, Marina Gorgete; Miranda, Bruno de; Cademartori, Pedro Henrique Gonzalez de (Floresta, 2021)
A simple method to extract pyrolytic lignin from bio-oil is under agitation in water or organic solvent. This process produces a water-insoluble fraction (pyrolytic lignin) and a water-soluble fraction (WS). In this study, we used a physical fractionation technique with water as a liquid agent to separate the two fractions of the fast pyrolysis bio-oil and obtain the WS — the object of study — to test its efficiency as a protective agent for lignocellulosic materials. The study aimed to investigate the efficiency of the aqueous phase (WS) as a water-repellent agent when impregnated into Pinus elliotti wood. To obtain WS, we used two bio-oil:water ratios (1:50 and 1:100) and two agitation speeds (17,000 and 8,500 RPM); they were respectively named WS50 and WS100, both with an average yield of 61% WS. Gas chromatography coupled with mass spectrometry (GC-MS), thermogravimetry (TGA), contact angle, and scanning electron microscopy (SEM) were used to characterize the WS and the veneers impregnated with it. There were no morphological changes on their surface, especially regarding the non-coating of the wood pits; meanwhile, the TGA showed visible changes in the degree of thermal degradation of the impregnated material related to the chemical composition of the WS identified in the GC-MS. There was a significant increase, on average 62%, in the apparent contact angle of the impregnated wood, approximately 126°. The WS has shown to be efficient as a protective agent by converting the hydrophilic surface of Pinus elliotti into a hydrophobic one, and this effect partially remained after 45 days of exposure.